1972
DOI: 10.1107/s0567740872002894
|View full text |Cite
|
Sign up to set email alerts
|

A refinement of the crystal structure of histidine hydrochloride monohydrate

Abstract: The crystal structure of histidine hydrochloride monohydrate has been refined. The crystals are orthorhombic P21212~, a= 15.301 (3), b= 8.921 (2), c= 6.846 (2) ~, Z=4. The intensities were measured with an automatic four-circle diffractometer using Mo K~ radiation. The structure was solved by the program SEARCHER, for the automatic heavy-atom analysis, and refined by full-matrix least-squares calculations to a final R of 0.037 for 1079 independent observed reflexions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

1973
1973
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 6 publications
3
31
0
Order By: Relevance
“…The lattice parameters are a = 6.849 Å, b = 8.928 Å, c = 15.302 Å and Volume = 935.685 Å 3 . The crystal data for LHC is presented in table 1 and it agrees well with the reported values [10]. FTIR spectroscopic analysis The recorded FTIR spectrum of LHC is as shown in figure 3.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The lattice parameters are a = 6.849 Å, b = 8.928 Å, c = 15.302 Å and Volume = 935.685 Å 3 . The crystal data for LHC is presented in table 1 and it agrees well with the reported values [10]. FTIR spectroscopic analysis The recorded FTIR spectrum of LHC is as shown in figure 3.…”
Section: Resultssupporting
confidence: 57%
“…LHC is one such promising semiorganic nonlinear optical material that belongs to the histidine-complex family which is isostructural to LHB [7]. A thorough scan of literature reveals that neutron and x-ray diffraction studies have already been reported [8,9], the compound was further refined on the basis of the intensity data collected by the diffractometer method [10]. The IR…”
Section: Introductionmentioning
confidence: 99%
“…Principal bond distances and bond angles are collected in Tables 2 and 3, respectively. D,L-Histidyl-L,D-histidine pentahydrate crystallizes in a zwitterionic form with protonation of the Cterminal imidazole ring. An intramolecular hydrogen bond exists between the two imidazole rings, N2D--H2D1.-.N1D = 2.724 (4),A, and 168 °, and is consistent with the study by Gorbitz (1989) Durif & Guitel, 1988;Edington & Harding, 1974;Kistenmacher, Hunt & Marsh, 1972;Lehmann, Koetzle & Hamilton, 1972;Madden, McGandy, Seeman, Harding & Hoy, 1972;Oda & Koyama, 1972;Bennett, Davidson, Harding & Morelle, 1970).…”
Section: Discussionsupporting
confidence: 88%
“…The bond distances and angles for the protonated imidazole ring are comparable to those found in the imidazolium cation (Blessing, 1986) or other histidinium cations (Averbuch-Pouchot, Durif & Guitel, 1988;Roman, Gutierrez-Zorrilla, Luque & Vegas, 1987;Blessing, 1986;Herbstein & Kapon, 1979;Fuess, Hohlwein & Mason, 1977;Oda & Koyama, 1972;Bennett, Davidson, Harding & Morelle, 1970;Donohue & Caron, 1964). The non-protonated imidazole ring has distances and angles comparable to imidazole (Martinez-Carrera, 1966) or other neutral histidine residues (Edington & Harding, 1974;Lehmann, Koetzle & Hamilton, 1972;Madden, McGandy, Seeman, Harding & Hoy, 1972).…”
Section: Discussionmentioning
confidence: 56%
“…In addition, bromide ion forms two more hydrogen bonds with neighboring amino groups and two weak C2H Á Á Á Br -type hydrogen bonds with imidazole group. Comparison with the structure of L-His Á HCl Á H 2 O [17,18] shows that they are isostructural. Dehydration of L-His Á HCl Á H 2 O and L-His Á HBr Á H 2 O occurs at 160 and 143 1C, respectively.…”
Section: L-his + Hbr + H 2 Omentioning
confidence: 93%